Effectiveness and Toxicity of Fractionated Proton Beam Radiotherapy for Cranial Nerve Schwannoma Unsuitable for Stereotactic Radiosurgery - Eichkorn, Tanja; Regnery, Sebastian; Held, Thomas; Kronsteiner, Dorothea; Hörner-Rieber, Juliane; El Shafie, Rami A.; Herfarth, Klaus; Debus, Jürgen; König, Laila (Frontiers in Oncology, 2021)
Purpose: In this benign tumor entity, preservation of cranial nerve function is of special importance. Due to its advantageous physical properties, proton beam radiotherapy (PRT) is a promising approach that spares healthy tissue. Could PRT go along with satisfactory preservation rates for cranial nerve function without compromising tumor control in patients with cranial nerve schwannoma unsuitable for stereotactic radiosurgery? Methods: We analyzed 45 patients with cranial nerve schwannomas who underwent PRT between 2012 and 2020 at our institution. Response assessment was performed by MRI according to RECIST 1.1 and toxicity was graded following CTCAE 5.0. Results: The most common schwannoma origin was the vestibulocochlear nerve with 82.2%, followed by the trigeminal nerve with 8.9% and the glossopharyngeal nerve as well as the vagal nerve, both with each 4.4%. At radiotherapy start, 58% of cranial nerve schwannomas were progressive and 95.6% were symptomatic. Patients were treated with a median total dose of 54 Gy RBE in 1.8 Gy RBE per fraction. MRI during the median follow-up period of 42 months (IQR 26 - 61) revealed in 93.3% of patients stable disease and in 6.7% partial regression. There was no case of progressive disease. New or worsening cranial nerve dysfunction was found in 20.0% of all patients, but always graded as CTCAE °I-II. In seven cases (16%) radiation induced brain lesions (RIBL) were detected after a median time of 14 months (range 2 - 26 months). RIBL were asymptomatic (71%) or transient symptomatic (CTCAE °II; 29%). No CTCAE °III/IV toxicities were observed. Lesions regressed during follow-up period in 3 of 7 cases and no lesion progressed during follow-up period. Conclusion: These data demonstrate excellent effectiveness with 100% local control in a median follow-up period of 3.6 years with a promising cranial nerve functional protection rate of 80%. RIBL occurred in 16% of patients after PRT and were not or only mild symptomatic but made a short course of dexamethasone necessary.